Perceived causes and prevention of catheter-associated urinary tract infections among spinal cord injured patients - O, Malomo Adefolarin; Kafayat, Aminu; A, Adeolu Augustine; O, Adeleye Amos; A, Balogun James; A, Badejo Oluwakemi; T, Shokunbi Mathew; S, Jegede Ayodele (Journal of Clinical Nephrology, 2019)
Catheter-associated urinary tract infection (CAUTI) is among the most common nosocomial infections especially in acute care settings. Its economic and unanticipated health implications make it burdensome for the healthcare providers and patients. The paper examined the perceived causes and mode of preventing urinary tract infections in patients with spinal cord injury. Qualitative research approach was utilized; the study site was a Tertiary Hospital in Nigeria. Eight (8) in-depth interviews (IDI) were conducted with healthcare providers managing patients with spinal cord injured in the hospital. The major risk factors causing urinary tract infection identified include financial problems, organization of care, human error, hospital environment and patient-related factors. To prevent urinary tract infections among patients in the hospital, a number of suggestions were made by the participants such as training of caregivers and educating patients and relations. The authors concluded that the incidence of CAUTI could be reduced in the hospital if the opinions of stakeholders are fairly considered.